High-density polyethylene composite additive and preparation method thereof
By using composite additives embedded in microcapsules with antioxidants in high-density polyethylene, the aging problem of high-density polyethylene materials under light, heat and oxygen is solved, and the long-term antioxidant performance of the material is achieved and the improved aging resistance of the material is achieved.
Patent Information
- Application Number
- CN202510397409.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-01
AI Technical Summary
During processing and use, high-density polyethylene materials are easily affected by factors such as light, heat, and oxygen, resulting in changes in molecular structure, gradually becoming brittle, deteriorating mechanical properties and aging resistance, and shortening service life.
A high-density polyethylene composite additive is adopted, which contains an aging-resistant agent, a fluoropolymer and an antistatic agent. The aging-resistant agent is composed of an antioxidant as the capsule core and a microcapsule with urea formaldehyde resin doped with titanium dioxide and silica nanoparticles as the capsule wall. Through the protection and slow release mechanism of the microcapsule, the dispersion and utilization efficiency of the antioxidant are improved.
It extends the service life of antioxidants, realizes the long-term antioxidant properties of high-density polyethylene, improves the material's aging resistance, processing performance and mechanical properties, and extends its service life.
Smart Images

Figure CN119912728A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polyethylene composite additives, and in particular to a high-density polyethylene composite additive and a preparation method thereof. Background Art
[0002] High-density polyethylene is a crystalline polymer material with low price and excellent mechanical properties. It is insoluble in organic solvents at room temperature, resistant to corrosion by acids, alkalis and salts, has stable chemical properties, good wear resistance, electrical insulation, toughness and cold resistance, and is mainly used in packaging, construction, wires and cables, pipelines and other fields. However, high-density polyethylene materials are easily affected by factors such as light, heat, and oxygen during processing and use, resulting in changes in molecular structure, gradual brittleness, decreased mechanical properties and aging resistance, and shortened service life.
[0003] In recent years, with the continuous expansion of the application fields of high-density polyethylene, the market demand for high-performance high-density polyethylene has been growing. However, the expensive price of imported high-density polyethylene additives has limited their promotion and application. Therefore, the development of efficient high-density polyethylene composite additives to improve the aging resistance, mechanical properties, processing properties, etc. of high-density polyethylene has received more and more attention.
[0004] At present, HDPE composite additives mainly include antioxidants, UV inhibitors, stabilizers, lubricants, plasticizers, antistatic agents, etc. These additives improve the aging resistance, mechanical properties and processing properties of HDPE through different mechanisms. However, there may be problems such as poor synergy and poor dispersibility between these additives, resulting in unstable quality and poor performance of HDPE materials.
[0005] The patent application document with publication number CN115286839A discloses a highly UV-resistant special polyethylene composite additive, whose components include antioxidants, low-density polyethylene and nanoparticles, wherein the nanoparticles are prepared by ball-milling zinc oxide, titanium dioxide and silicon dioxide in a certain molar ratio. During the preparation, the raw materials are mixed evenly under a nitrogen atmosphere and then added to a twin-screw extruder for melting, plasticizing, extrusion and granulation. In this way, since the antioxidants and nanoparticles are in powder form, their dispersibility in low-density polyethylene is poor, which may affect the aging resistance of low-density polyethylene. Summary of the invention
[0006] In order to improve the aging resistance of high-density polyethylene, the present application provides a high-density polyethylene composite additive and a preparation method thereof.
[0007] A high-density polyethylene composite auxiliary agent, comprising the following components in parts by weight: 50-80 parts of an anti-aging agent, 1-5 parts of a fluoropolymer, and 1-10 parts of an antistatic agent; The preparation method of the anti-aging agent comprises the following steps: S1: dissolve urea in water, add formaldehyde, stir, adjust the pH to 8-9, react at 70-75°C for 0.5-3h, cool to room temperature, and obtain a mixed solution A; S2: adding tetrabutyl titanate, tetraethyl orthosilicate and ethanol to the mixed solution A, stirring for 1-3 hours, and obtaining a mixed solution B; S3: Mix the antioxidant, emulsifier and water at 35-50°C, add the mixed solution B, stir for 5-10 minutes, adjust the pH value to 3-5, react at 60-65°C for 2-5 hours, filter and dry.
[0008] In the above technical solution, the anti-aging agent is a microcapsule with an antioxidant as the capsule core and a urea-formaldehyde resin doped with titanium dioxide and silicon dioxide nanoparticles as the capsule wall. On the one hand, the antioxidant is embedded in the microcapsule, which can firstly protect the antioxidant and prevent the antioxidant from being affected by light, heat and oxygen during the processing and use of high-density polyethylene, thereby extending the service life of the antioxidant; secondly, it can achieve the slow release of the antioxidant, avoid the antioxidant from being consumed prematurely, improve the utilization efficiency of the antioxidant, and make the high-density polyethylene have long-lasting antioxidant properties; finally, it can improve the dispersibility of the antioxidant, so that the antioxidant can be evenly distributed in the high-density polyethylene, reducing the performance degradation caused by uneven dispersion.
[0009] Secondly, in the outdoor atmospheric environment, high-density polyethylene is easily exposed to ultraviolet rays, which triggers photo-oxidation reactions and causes the high-density polyethylene to age and degrade. In order to reduce the aging and degradation of high-density polyethylene, an anti-ultraviolet agent that can absorb or scatter ultraviolet rays to achieve a shielding effect is introduced into the microcapsule. Titanium dioxide nanoparticles have good absorption, reflection and scattering capabilities for ultraviolet rays. When exposed to ultraviolet rays, the electrons in the nano-titanium dioxide are excited and transition from the valence band to the conduction band, causing the absorption of ultraviolet rays. Since the particle size of nano-titanium dioxide is small and the number is large, it has a strong absorption capacity for ultraviolet rays and can also block ultraviolet rays by reflection and scattering. In addition, nano-silicon dioxide has a large specific surface area and high activity, and can also effectively shield ultraviolet rays; moreover, nano-silicon dioxide also has anti-adhesion properties, which can reduce the adhesion between high-density polyethylene molecules, reduce the tendency of adhesion, and improve the processing fluidity of high-density polyethylene. In summary, introducing nano-silicon dioxide and nano-titanium dioxide into microcapsules can not only enhance the stability of microcapsules, improve the strength and toughness of high-density polyethylene, but also improve the aging resistance and processing performance of high-density polyethylene.
[0010] Thirdly, urea-formaldehyde resin is made into microcapsules and added to high-density polyethylene, which can improve its dispersibility in high-density polyethylene, make it evenly distributed in high-density polyethylene, and reduce the performance differences caused by uneven distribution; moreover, urea-formaldehyde resin embeds antioxidants inside it, so that nano-titanium dioxide and nano-silicon dioxide are doped in its molecules, which can reduce the mutual influence between antioxidants and nano-titanium dioxide and nano-silicon dioxide and improve their synergistic effect; in addition, urea-formaldehyde resin contains more hydrogen bonds. When affected by light, heat and oxygen, the molecular chains of high-density polyethylene break, which can be repaired to a certain extent by rebuilding the hydrogen bonds in the urea-formaldehyde resin, thereby improving the aging resistance of high-density polyethylene, reducing the degradation rate and extending the service life.
[0011] Preferably, the fluoropolymer is one or more of fluoropolymer FX5922, fluoropolymer FX5917 and fluoropolymer FX9613.
[0012] In the above technical solution, fluoropolymer is a straight-chain alkane polymer, and part or all of the hydrogen atoms in its molecular structure are replaced by fluorine. Therefore, fluoropolymer has a lower surface energy, and can effectively reduce the friction between the melt and the mold during the processing of high-density polyethylene, thereby reducing shear stress and inhibiting the occurrence of melt fracture. In addition, due to the flexibility and low viscosity of the fluoropolymer molecular chain, fluoropolymer can act as a plasticizer, making the high-density polyethylene more fluid during the processing, thereby helping the high-density polyethylene melt to be evenly distributed in the mold and reducing surface roughening.
[0013] Preferably, the antistatic agent is bis(β-hydroxyethyl)coconut amine.
[0014] Preferably, in step S1, the mass ratio of urea to formaldehyde is 1:(1.5-3).
[0015] Preferably, the mass ratio of urea, tetrabutyl titanate and tetraethyl orthosilicate is 1:(0.2-0.5):(0.1-0.3).
[0016] Preferably, in step S3, the antioxidant consists of a phenolic antioxidant and a phosphite antioxidant, and the mass ratio of the phenolic antioxidant to the phosphite antioxidant is 1:(0.1-0.5).
[0017] By adopting the above technical scheme, firstly, the phenolic hydroxyl group in the phenolic antioxidant has high activity, can quickly combine with free radicals, prevent the oxidative degradation reaction from proceeding, and has good thermal stability and compatibility, and can continuously play an antioxidant role during the processing and use of high-density polyethylene. Secondly, the phosphite antioxidant can decompose the hydroperoxides produced during the processing of high-density polyethylene, prevent it from further decomposing to produce free radicals, and then inhibit the breakage of polymer chains. With phenolic antioxidant as the main component and phosphite antioxidant as the auxiliary component, the aging resistance of high-density polyethylene can be synergistically improved.
[0018] Preferably, the phenolic antioxidant is one or more of antioxidant 1010, antioxidant 264 and antioxidant 1076; the phosphite antioxidant is one or more of antioxidant DSTP, antioxidant 242 and antioxidant 168.
[0019] Preferably, in step S2, the emulsifier is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and sodium hexadecyl sulfate.
[0020] Preferably, the mass ratio of urea to antioxidant is 1:(2.2-4.8).
[0021] A method for preparing a high-density polyethylene composite additive comprises the following steps: The various component raw materials of the high-density polyethylene composite additive are mixed evenly and extruded into granules.
[0022] In the above technical scheme, the raw materials of the composite additives of high-density polyethylene are mixed evenly and then extruded and granulated to make composite additive particles, which are then added to high-density polyethylene. This can improve the dispersibility of the composite additives in the high-density polyethylene and reduce the agglomeration phenomenon caused by uneven mixing during the addition of each additive separately, thereby improving the quality uniformity and stability of the high-density polyethylene; moreover, the composite additives are added in the form of particles, which reduces the difficulty of mixing the powdered additives or liquid additives and improves production efficiency.
[0023] The above technical solution of the present application includes at least the following beneficial effects: 1. The present application embeds the antioxidant in the microcapsule, which can not only protect the antioxidant and prolong the service life, but also realize the slow release of the antioxidant, so that the high-density polyethylene has long-lasting antioxidant properties; in addition, it can also improve the dispersibility of the antioxidant and reduce agglomeration.
[0024] 2. In the process of preparing microcapsules, the present application uses urea-formaldehyde resin doped with nano-titanium dioxide and nano-silicon dioxide as the capsule wall, which can not only enhance the stability of the microcapsules, but also give play to the synergistic effect of nano-titanium dioxide and nano-silicon dioxide, improve the aging resistance and processing performance of high-density polyethylene, and also has a certain self-repairing effect, further improving the aging resistance of high-density polyethylene.
[0025] 3. The present application prepares high-density polyethylene composite additives into particles, which can improve the dispersibility of the composite additives in high-density polyethylene, reduce the difficulty of mixing between each additive and high-density polyethylene, and thus improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is the tensile strength retention rate of high-density polyethylene specimens after aging test. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0029] Example Example 1 The high-density polyethylene composite additive of this embodiment comprises the following components in parts by weight: 50 parts of anti-aging agent, 1 part of fluoropolymer, and 10 parts of antistatic agent; The preparation method of the anti-aging agent in this embodiment comprises the following steps: S1: Weigh 10 g of urea, dissolve it in 100 mL of deionized water, add 50 g of 30% formaldehyde solution, use a magnetic stirrer, adjust the speed to 400 r / min, adjust the pH to 8, react at 70 ° C for 3 h, cool to room temperature, and obtain a mixed solution A; S2: Slowly add 2 g of tetrabutyl titanate, 1 g of tetraethyl orthosilicate and 20 mL of ethanol into the mixed solution A, adjust the stirring speed to 150 r / min, and continue stirring for 1 h to obtain a mixed solution B; S3: Weigh 1g of antioxidant 1010, 1g of antioxidant 264, 0.2g of antioxidant DSTP, 0.5g of sodium dodecylbenzene sulfonate and 50g of deionized water, mix them evenly at 40°C, add mixed solution B, stir for 5min, adjust the pH value to 3 with dilute hydrochloric acid, react at 60°C for 5h, filter and dry after the reaction is completed; The preparation method of the high-density polyethylene composite additive in this embodiment comprises the following steps: Weigh 500g of an anti-aging agent, 10g of fluoropolymer FX5922 and 100g of bis(β-hydroxyethyl)coconut amine, stir and mix at room temperature at a stirring speed of 150r / min for 5min, and then put the mixture into an extrusion granulator for granulation.
[0030] Example 2 The high-density polyethylene composite additive of this embodiment comprises the following components in parts by weight: 80 parts of anti-aging agent, 5 parts of fluoropolymer, and 1 part of antistatic agent; The preparation method of the anti-aging agent in this embodiment comprises the following steps: S1: Weigh 10 g of urea, dissolve it in 100 mL of deionized water, add 100 g of 30% formaldehyde solution, use a magnetic stirrer, adjust the speed to 400 r / min, adjust the pH to 9, react at 75 ° C for 0.5 h, cool to room temperature, and obtain a mixed solution A; S2: Slowly add 2 g of tetrabutyl titanate, 1 g of tetraethyl orthosilicate and 20 mL of ethanol into the mixed solution A, adjust the stirring speed to 150 r / min, and continue stirring for 3 h to obtain a mixed solution B; S3: weigh 1g of antioxidant 1076, 1g of antioxidant 264, 0.1g of antioxidant DSTP, 0.1g of antioxidant 168, 0.5g of sodium dodecyl sulfate and 50g of deionized water, mix them evenly at 40°C, add mixed solution B, stir for 10min, adjust the pH value to 5 with dilute hydrochloric acid, react at 65°C for 2h, filter and dry after the reaction is completed; The preparation method of the high-density polyethylene composite additive in this embodiment comprises the following steps: Weigh 800g of anti-aging agent, 50g of fluoropolymer FX5917 and 10g of bis(β-hydroxyethyl)coconut amine, stir and mix them at room temperature at a stirring speed of 150r / min for 5min, and then put the mixture into an extrusion granulator for granulation.
[0031] Example 3 The high-density polyethylene composite additive of this embodiment comprises the following components in parts by weight: 65 parts of anti-aging agent, 3 parts of fluoropolymer, and 5 parts of antistatic agent; The preparation method of the anti-aging agent in this embodiment comprises the following steps: S1: Weigh 10 g of urea, dissolve it in 100 mL of deionized water, add 80 g of 30% formaldehyde solution, use a magnetic stirrer, adjust the speed to 400 r / min, adjust the pH to 9, react at 75 ° C for 0.5 h, cool to room temperature, and obtain a mixed solution A; S2: Slowly add 2 g of tetrabutyl titanate, 1 g of tetraethyl orthosilicate and 20 mL of ethanol into the mixed solution A, adjust the stirring speed to 150 r / min, and continue stirring for 2 h to obtain a mixed solution B; S3: weigh 1g of antioxidant 1076, 1g of antioxidant 1010, 0.1g of antioxidant 242, 0.1g of antioxidant 168, 0.5g of sodium hexadecyl sulfate and 50g of deionized water, mix them evenly at 40°C, add mixed solution B, stir for 10min, adjust the pH value to 4 with dilute hydrochloric acid, react at 65°C for 2h, filter and dry after the reaction is completed; The preparation method of the high-density polyethylene composite additive in this embodiment comprises the following steps: Weigh 650g of anti-aging agent, 10g of fluoropolymer FX5917, 20g of fluoropolymer FX9613 and 50g of bis(β-hydroxyethyl)coconut amine, stir and mix at room temperature at a stirring speed of 150r / min for 5min, and then put the mixture into an extrusion granulator for granulation.
[0032] Example 4 The weight components of the high-density polyethylene composite additive of this embodiment are the same as those of Example 3; The preparation method of the anti-aging agent of this embodiment is different from that of embodiment 3 in that: S2: Slowly add 5 g of tetrabutyl titanate, 3 g of tetraethyl orthosilicate and 20 mL of ethanol into the mixed solution A, adjust the stirring speed to 150 r / min, and continue stirring for 2 h to obtain a mixed solution B; The remaining steps are the same as those in Example 3; The preparation method of the high-density polyethylene composite additive in this embodiment is the same as that in Example 3.
[0033] Example 5 The weight components of the high-density polyethylene composite additive of this embodiment are the same as those of Example 4; The preparation method of the anti-aging agent of this embodiment is different from that of embodiment 4 in that: S3: Weigh 2g of antioxidant 1076, 1.2g of antioxidant 1010, 0.8g of antioxidant 242, 0.8g of antioxidant 168, 0.5g of sodium hexadecyl sulfate and 50g of deionized water, mix them evenly at 40°C, add mixed solution B, stir for 10min, adjust the pH value to 4 with dilute hydrochloric acid, react at 65°C for 2h, filter and dry after the reaction is completed, and the mixture is ready: The remaining steps are the same as those in Example 4; The preparation method of the high-density polyethylene composite additive in this embodiment is the same as that in Example 4.
[0034] Example 6 The weight components of the high-density polyethylene composite additive of this embodiment are the same as those of Example 4; The preparation method of the anti-aging agent of this embodiment is different from that of embodiment 4 in that: S3: Weigh 2g of antioxidant 1076, 1g of antioxidant 1010, 0.5g of antioxidant 242, 0.4g of antioxidant 168, 0.5g of sodium hexadecyl sulfate and 50g of deionized water, mix them evenly at 40°C, add mixed solution B, stir for 10min, adjust the pH value to 4 with dilute hydrochloric acid, react at 65°C for 2h, filter and dry after the reaction is completed, and the mixture is ready: The remaining steps are the same as those in Example 4; The preparation method of the high-density polyethylene composite additive in this embodiment is the same as that in Example 4.
[0035] Comparative Example Comparative Example 1 The high-density polyethylene composite additive of this comparative example comprises the following components in parts by weight: 45 parts of urea-formaldehyde resin, 1 part of nano titanium dioxide, 0.5 parts of nano silicon dioxide, 1.5 parts of antioxidant 1010, 1.5 parts of antioxidant 264, 0.5 parts of antioxidant DSTP, 1 part of fluoropolymer FX5922, and 10 parts of bis(β-hydroxyethyl) coconut amine; The preparation method of the high-density polyethylene composite additive in this comparative example comprises the following steps: Weigh 450g of urea-formaldehyde resin, 10g of nano-titanium dioxide, 5g of nano-silicon dioxide, 15g of antioxidant, 15g of antioxidant 264, 5g of antioxidant DSTP, 10g of fluoropolymer FX5922 and 100g of bis(β-hydroxyethyl)coconut amine, stir and mix at room temperature at a stirring speed of 150r / min for 5min, and then put the mixture into an extrusion granulator for granulation.
[0036] Performance testing Aging resistance test 1. Sample preparation: 100 g of the high-density polyethylene composite additives of Examples 1-6 and Comparative Example 1 and 1 kg of high-density polyethylene were mixed and stirred evenly under a nitrogen atmosphere, added to a twin-screw extruder for melting, plasticization, and extrusion, the melting temperature was 180°C, the screw speed was 50 r / min, and a 100 mm × 100 mm × 0.1 mm sample was made for aging resistance test. At the same time, pure high-density polyethylene, that is, high-density polyethylene without adding composite additives, was used as a blank experiment; 2. Light aging test steps: Use a spherical mercury xenon lamp with a UV radiation wavelength less than 365nm. After irradiating the above samples for 15 days, perform a tensile performance test at a tensile rate of 50mm / min. The results of the tensile strength retention rate are as follows: Figure 1 As shown; 3. Heat aging test steps: Place the above samples in the same blast drying oven and age them at 120°C for 30 days before conducting a tensile performance test. The tensile rate is 50 mm / min. The results of the tensile strength retention are as follows: Figure 1 shown.
[0037] Results Analysis from Figure 1 It can be seen that compared with the blank experiment, the tensile strength retention rate of the high-density polyethylene samples in the comparative example and the embodiment is higher, indicating that the aging resistance is better.
[0038] from Figure 1 It can be seen from the data of Comparative Example 1 and Examples 1-3 that the high-density polyethylene composite auxiliary agent obtained by the preparation method of Examples 1-3 can better improve the aging resistance of high-density polyethylene, and with the increase in the amount of anti-aging agent added, the aging resistance is first improved and then basically remains unchanged. This may be because the encapsulation effect of the microcapsule on the antioxidant is more conducive to improving the dispersibility and stability of the antioxidant, thereby improving its long-term utilization rate; and, after the urea-formaldehyde resin is hybridized with nano-titanium dioxide and nano-silicon dioxide, it is more conducive to improving the dispersibility and stability of nano-titanium dioxide and nano-silicon dioxide, thereby being more conducive to improving its shielding performance against ultraviolet rays; in addition, the formation of microcapsules is also conducive to improving the tensile properties of high-density polyethylene.
[0039] from Figure 1 It can be seen from the data of Examples 3-6 that with the increase of the content of nano-titanium dioxide and nano-silicon dioxide in the anti-aging agent, the aging resistance of high-density polyethylene is improved; and the combination of phenolic antioxidants and phosphite antioxidants in the antioxidants is also more conducive to improving the aging resistance of high-density polyethylene.
[0040] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-density polyethylene composite additive, characterized in that: The composition comprises the following components in parts by weight: 50-80 parts of an anti-aging agent, 1-5 parts of a fluoropolymer, and 1-10 parts of an antistatic agent; The preparation method of the anti-aging agent comprises the following steps: S1: dissolve urea in water, add formaldehyde, stir, adjust the pH to 8-9, react at 70-75°C for 0.5-3h, cool to room temperature, and obtain a mixed solution A; S2: adding tetrabutyl titanate, tetraethyl orthosilicate and ethanol to the mixed solution A, stirring for 1-3 hours, and obtaining a mixed solution B; S3: Mix the antioxidant, emulsifier and water at 35-50°C, add the mixed solution B, stir for 5-10 minutes, adjust the pH value to 3-5, react at 60-65°C for 2-5 hours, filter and dry.
2. The high-density polyethylene composite auxiliary agent according to claim 1, characterized in that The fluoropolymer is one or more of fluoropolymer FX5922, fluoropolymer FX5917 and fluoropolymer FX9613.
3. The high-density polyethylene composite auxiliary agent according to claim 1, characterized in that The antistatic agent is bis(β-hydroxyethyl) coconut amine.
4. The high-density polyethylene composite auxiliary agent according to claim 1, characterized in that In step S1, the mass ratio of urea to formaldehyde is 1:(1.5-3).
5. The high-density polyethylene composite auxiliary agent according to claim 1, characterized in that: The mass ratio of urea, tetrabutyl titanate and tetraethyl orthosilicate is 1:(0.2-0.5):(0.1-0.3).
6. The high-density polyethylene composite auxiliary agent according to claim 1, characterized in that: In step S3, the antioxidant is composed of a phenolic antioxidant and a phosphite antioxidant, and the mass ratio of the phenolic antioxidant to the phosphite antioxidant is 1:(0.1-0.5).
7. The high-density polyethylene composite auxiliary agent according to claim 6, characterized in that: The phenolic antioxidant is one or more of antioxidant 1010, antioxidant 264 and antioxidant 1076; the phosphite antioxidant is one or more of antioxidant DSTP, antioxidant 242 and antioxidant 168.
8. The high-density polyethylene composite auxiliary agent according to claim 1, characterized in that: In step S2, the emulsifier is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and sodium hexadecyl sulfate.
9. The high-density polyethylene composite auxiliary agent according to claim 1, characterized in that: The mass ratio of the urea to the antioxidant is 1:(2.2-4.8).
10. A method for preparing a high-density polyethylene composite additive according to claim 1, characterized in that: The steps include: The various component raw materials of the high-density polyethylene composite additive are mixed evenly and extruded into granules.
Citation Information
Patent Citations
Super large caliber and non-excavation-use PE pollution discharge tubular product and manufacturing method thereof
CN101526159A
High-density polyethylene compound additive and preparation method thereof
CN103819802A
Microcapsule flame retardant as well as preparation method and application thereof
CN114085429A
Oil shale semicoke-based weather-resistant low-cost mulching film and preparation method thereof
CN119192629A